Ant-associated rove beetles (Coleoptera: Staphylinidae) in Bulgaria - Lapeva-Gjonova, Albena (Acta entomologica slovenica (Ljubljana), 2012)
The data on the findings of 33 species of rove beetles (Coleoptera, Staphylinidae) in the nests of 11 ant species in several regions of Bulgaria are reported. Seven species of Staphylinidae are new for the Bulgarian fauna: Quedius brevis Erichson, 1840, Oligota pumilio Kiesenwetter, 1858, Euryusa sinuata Erichson, 1837, Dinarda maerkelii Kiesenwetter, 1843, Oxypoda formiceticola Märkel, 1841, Thiasophila angulata (Erichson, 1837) and Piochardia reitteri (Wasmann, 1894). This is also the first time when species of the genus Piochardia have been found in the country. Data about new ant hosts and localities are reported and ethological categories are discussed. Ofthe species identified, synoeketes (14 species) and facultative myrmecophiles (13 species) are the most numerous. There are also three species of synechthrans, one species of a symphile, and two non-myrmecophilous species. The finding of numerous specimens of facultative species in the nests raises the question of their accidental entrance.
Keywords: ants; Bolgarija; Bulgaria; mirmekofili; mravlje; myrmecophiles; Staphylinidae